2017
DOI: 10.1186/s40635-017-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax immune globulin improves hemodynamics and survival during B. anthracis toxin-induced shock in canines receiving titrated fluid and vasopressor support

Abstract: BackgroundAlthough anthrax immune globulin (AIG) improved survival in antibiotic-treated Bacillus anthracis-challenged animal models, whether it adds to the benefit of conventional hemodynamic support for B. anthracis toxin-associated shock is unknown.MethodsWe therefore tested AIG in sedated, mechanically ventilated canines challenged with 24-h B. anthracis lethal and edema toxin infusions and supported for 96 h with a previously demonstrated protective regimen of titrated normal saline and norepinephrine.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…We conducted six studies in a canine model, first examining the effects of LT and ET challenges alone (Study 1) or together (Study 2) on survival, hemodynamic function and organ injury, and then the effects of either Raxibacumab (Studies 3, 4 and 5) or AIG (Study 6) when combined with titrated hemodynamic support (HS) on these same parameters ( Table 4 ) [ 16 , 17 , 18 , 27 ]. Prior studies suggested that these humanized or human antibodies would bind to canine cells and be effective.…”
Section: Effects Of the Raxibacumab And Aigiv When Combined With Tmentioning
confidence: 99%
See 4 more Smart Citations
“…We conducted six studies in a canine model, first examining the effects of LT and ET challenges alone (Study 1) or together (Study 2) on survival, hemodynamic function and organ injury, and then the effects of either Raxibacumab (Studies 3, 4 and 5) or AIG (Study 6) when combined with titrated hemodynamic support (HS) on these same parameters ( Table 4 ) [ 16 , 17 , 18 , 27 ]. Prior studies suggested that these humanized or human antibodies would bind to canine cells and be effective.…”
Section: Effects Of the Raxibacumab And Aigiv When Combined With Tmentioning
confidence: 99%
“…Each study we conducted was approved by the National Institutes of Health Clinical Center’s Animal Care and Use Committee [ 16 , 17 , 18 , 27 ]. In individual weekly experiments comprising the studies, three or four purpose-bred beagles were continuously sedated, mechanically ventilated via tracheostomies and had systemic, pulmonary and urinary catheters in place.…”
Section: Effects Of the Raxibacumab And Aigiv When Combined With Tmentioning
confidence: 99%
See 3 more Smart Citations